An Application Model for the Effective Implementation of a Project Quality Plan - Mohammed, Abdul Hakim (CRES, FKSG, 2006)
This paper reports the development of an application model for effective implementation of a project quality plan in large construction projects. The model was derived out of a case study undertaken at Kuala Lumpur International Airport (KLIA), a prestigious multibillion dollars project commissioned by the government of Malaysia. The complete history of the ISO implementation in KLIA starting from the inception of the project until its completion was studied through several means including a series of interviews with staff, and archival studies of quality records and voluminous implementation documents. This paper, while initially highlighting the pitfalls observed in the implementation stage and other major problems as identifiedfromthequalityrecords,finallyfocusesontheapplicationmodel.Havingobserved the overall problem background and success and failure stories from the case studies, the application model was developed. The key participants of the KLIA including the Client’s Representative (KLIAB - Kuala Lumpur International Airport Berhad), Quality Consultants, Quality Management Department, and Contractors were involved in the research. The application model is conceptual and it broadly addresses the major issues that are critical to the implementation of the Project Quality Plan (PQP) in large construction projects. It should be seen as an aiding mechanism to improve the quality performance of the construction participants. It must also be noted that the model has been developed from the perspective of the Client (Owner).